2008
DOI: 10.1088/0960-1317/18/10/105010
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the electrical contact behaviors in Au-to-Au thin-film contacts for RF MEMS switches

Abstract: This paper presents the electrical contact behaviors of gold-to-gold thin-film contacts under high current conditions and describes the major factors that influence these contact behaviors for radio frequency microelectromechanical system switches. The fundamental phenomena in the contact resistance versus contact force curve were investigated with a contact measurement setup, which we devised. Based on the experimental results, the contact resistance behavior with increasing contact force can be divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 32 publications
2
37
0
Order By: Relevance
“…In addition, the contact temperature (Tc) of contact a-spots could be linked with the contact force depending on the contact voltage [5]. Indeed the plastic deformation of the asperities during the contact formation proceeds more rapidly when the softening temperature is reached [2].…”
Section: Contact Theory and Failure Mechanismsmentioning
confidence: 99%
“…In addition, the contact temperature (Tc) of contact a-spots could be linked with the contact force depending on the contact voltage [5]. Indeed the plastic deformation of the asperities during the contact formation proceeds more rapidly when the softening temperature is reached [2].…”
Section: Contact Theory and Failure Mechanismsmentioning
confidence: 99%
“…The best compromise between mechanical and electrical performances has to be found to reach reliable operations. The material must have good electrical conductivity to avoid losses, high melting point to handle power, appropriate hardness to avoid stiction, and chemical inertness to avoid oxidation [7]. This information can be partly found in the literature, but it does not replace a direct quantitative characterization of the MUT, as it is done by means of the setup presented in next subsection.…”
Section: D) Performances and Reliability Of Micro Contactsmentioning
confidence: 99%
“…11 Recent work on MEMS switches where simple hemisphere-on-flat systems are to simulate MEMS switch behavior, have shown that the Au-to-Au contact metal failure remains an important issue at the micrometer and nanometer scales. [12][13]14,15 Admittedly, macroscopic contact bounce phenomena inevitably occur during the contacts breaking. They are generally attributed to the mechanical reaction due to high force and high velocity applied to the mobile contact part during contact closure.…”
Section: Introductionmentioning
confidence: 99%